Excessive Use of the Internet and Its Relationship to Psychological Strikes among Young Football Players - Abbas Aideem, Najm; Neama Hassen, Oras; Jasim Hammood, Saad (International Journal of Psychosocial Rehabilitation, 2020)
The researchers touched on the introduction and the importance of the research and mentioned that the football game is one of the sports in which the players make a great physical effort throughout the period of the match, which leads to their exposure to great psychological pressure, and therefore the psychological factor has a great role in the progress and development of the level of the player. And health has a direct impact on its ability and performance in particular and on the team as a whole. As for the research problem, it was represented by the matter that prompted the researchers to conduct this study and search for its causes resulting from excessive use of the Internet that may lead to the destruction of the sports, moral, social, and health value system of the research sample being one of the teenage young players. The study aimed to build and legalize a questionnaire of excessive use of the Internet and psychological distress among young soccer players and to identify the relationship between them. The researchers used the descriptive approach in the two methods of surveying and correlational relations. The study sample consisted of 160 emerging players, and the sample was divided into two parts: a constructive sample of 100 players and an application sample of 60 players. The value of the Pearson correlation coefficient was found between the questionnaire for excessive use of interferon The Internet and the Psychiatric Disorder Questionnaire indicate a high correlation between the two variables under study. The Internet Excessive Use and Psychological Disorder Questionnaire is a tool to reveal the level of psychological and health status of emerging football players. Researchers recommend activating the role of control and directing players towards the optimal use of the Internet.